The Library of the Ethnographic Museum in Zagreb - Kolbas, Irena (Array, 2019)
The Library of the Ethnographic Museum is a special museum library. It is of a semi-closed type, which is the case with most special and museum libraries. It is primarily intended for the museum staff: curators, conservators and preparators. It was founded not long after the museum had been established and it grew simultaneously with the museum collection. The paper provides an overview of its history, some of its more important collections and the processing of the publications. Nevertheless, it also presents some of the problems faced.